Hukum Islam: Maslahah Mursalah Berdasarkan Perspektif Emapat Madzhab dan Ahli Ushul Fiqh - Zainal Aris Masruchi (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2023)
This research discusses how four schools of thought and ushul fiqh experts view maslahah murrasa from their perspective as a general benefit that can be applied in certain contexts. This research methodology uses a literature review approach in explaining the principles of maslahah murlah taken from scientific works. The data source for this research comes from digital libraries and consists of books, literature reviews, scientific papers and journals. The criteria for selecting data sources is high relevance to the research topic. This research uses content analysis and thematic techniques to extract information from the literature. The research results show that the benefits that arise in new conditions that are not explicitly explained by Sharia law or certain guidelines are called maslahah murlah. This is goodness that does not have a clear or deep legal basis (dalil), but is supported by many meanings in the texts (verses and hadith). In this situation, the benefit (al-munâsib) is in line with the principles of Sharia law. It is important to note that conformity with sharia actions does not always require support from a proposition that explicitly refers to those benefits. Rather, it can be collective and refer to a collection of propositions indicating definite benefits (qat'î). In cases where this definite postulate has a general meaning (kullî), the strength of the definite kullî postulate is considered to be equivalent to the strength of the particular postulate.